2011
DOI: 10.1117/1.3541796
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral coherent anti-Stokes Raman scattering microscopy imaging through turbid medium

Abstract: Abstract. Coherent Raman microspectroscopy imaging is an emerging technique for noninvasive, chemically specific optical imaging, which can be potentially used to analyze the chemical composition and its distribution in biological tissues. In this report, a hierarchical cluster analysis was applied to hyperspectral coherent anti-Stokes Raman imaging of different chemical species through a turbid medium. It was demonstrated that by using readily available commercial software (Cytospec, Inc.) and cluster analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…[15][16][17] So-called hyperspectral CARS microscopy enables efficient signal detection even in turbid media, because also nonballistic photons can be collected by large area single element detectors. [18] For real-time detection of spectral changes, extremely fast tunable laser sources are required. The work presented here aims at the presentation of a compact fiber laser source for the before mentioned approach of hyperspectral CARS microscopy utilizing fast spectrally tuneable narrow band lasers.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] So-called hyperspectral CARS microscopy enables efficient signal detection even in turbid media, because also nonballistic photons can be collected by large area single element detectors. [18] For real-time detection of spectral changes, extremely fast tunable laser sources are required. The work presented here aims at the presentation of a compact fiber laser source for the before mentioned approach of hyperspectral CARS microscopy utilizing fast spectrally tuneable narrow band lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, random Raman lasing gives us an opportunity to study nonlinear optical effects in a turbid media. A better knowledge of these dynamics will help improve upon applications ranging from chemical analysis in turbid media [1921] to stimulated Raman induced photoacoustics [2224]. …”
Section: Introductionmentioning
confidence: 99%
“…One important consideration for quantitative CARS spectroscopy is to overcome spectral distortion caused by nonresonant background. Excellent research has shown the ability to acquire useful Raman information by effectively subtracting nonresonant CARS signal using various methods such as heterodyne detection, , maximum entropy method, and a modified Kramers–Krönig transformation. ,, Another important direction of quantitative CARS microscopy is to sort spectral information into groups to derive chemical composition maps for complicated systems using methods such as principle component analysis, hierarchical cluster analysis, classical least-squares analysis, and singular value decomposition analysis . Additionally, since one of the most important advantages of vibrational spectroscopic techniques is the ability to elucidate complicated molecular structures based on quantitative spectral analysis, CARS has been used to study molecular orientations in a specimen.…”
mentioning
confidence: 99%